Current status of robotic surgery for colorectal cancer: A review - Won Beom Jung (International Journal of Gastrointestinal Intervention, 2022)
The number of robot-assisted colorectal surgeries is increasing because these robotic devices afford surgeon-controlled, high-definition, and three-dimensional vision during surgery and have sophisticated, angulated arms with remarkable ergonomics and a great degree of range. Nevertheless, robotic colorectal surgery has been praised and criticized simultaneously because its superiority over laparoscopic surgery in terms of outcomes has not been clearly shown. Despite its numerous advantages, several studies have failed to reveal the supremacy of robotic surgery over laparoscopic surgery regarding oncologic and postoperative outcomes. Additionally, robotic surgery is more expensive and is associated with a longer operative time than laparoscopic surgery. Regardless of research findings, many surgeons perform robotic colorectal surgeries. Therefore, this review will evaluate the benefits and drawbacks of robotic surgery for colorectal cancer through recent studies and reviews. The indications for the robotic approach are increasing. Therefore, further research should be conducted to accurately assess the relevance of robotic surgery for colorectal cancer.